Good governance and good aid allocation - Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2008)
We model the aid allocation decision where the donor government has announced that good governance is the criterion for receiving aid. Potential recipients must compete for the aid funds. The structure of the competition is important to the donor in terms of achieving good governance, and to the recipients in terms of what they receive. The leaders of potential recipient countries look at aid availability through this contest as part of the competing objectives they face - some good, some not good. The donor country prefers a contest under which the aid will only go to one country while the leaders of the receiving countries prefer that each country obtains the proportion of aid relative to its governance quality. If poverty reduction is an independent goal as well, a poverty trap may be created. With good governance as a criterion, donors may work through both bilateral and multilateral agencies.
urn:nbn:de:101:1-20080711104
Keywords: O10; 330; Foreign aid; governance; decentralization; rent seeking; Entwicklungshilfe; Entwicklungshilfekonditionen; Good Governance; Wettbewerb; Rent Seeking; Entwicklungskooperation; Dezentralisierung; Theorie